Development of semi-synthetic diet for laboratory rearing of western corn borer (Ostrinia spp.) in Kobe, Japan - Pokhrel, S; Wijarn, S (Agronomy Journal of Nepal, 2013)
A pair wise experiment was conducted, aiming to develop an artificial diet for laboratory rearing of Ostrinia species and for understanding their developmental characteristics in the control environment in insect physiology lab, Kobe University, Japan. Eleven different diets with various recipes were tested to observe the performance of diets and to evaluate the developmental characteristics of three Ostrinia species. In general, the survival was highest with O zaguliaevi adapted nearly all diets we prepared, O furnacalis survived fairy well but none of the diet was found satisfactory for rearing O scapulalis. The period of larval stage was shortest in O zaguliaevi, longest in O furnacalis and intermediate in O scapulalis. Photoperiodism was observed with both O scapulalis and O furnacalis. The type of photoperiodoic response was a typical long day type. Different diet resulted in one hour difference in the critical photoperiod in case of O scapulalis. DOI: http://dx.doi.org/10.3126/ajn.v1i0.7549 Agronomy Journal of Nepal (Agron JN) Vol. 1: 2010 pp.103-106